Evaluasi Usability dan Perbaikan Rancangan Situs Web Laroslaptop.com Menggunakan Metode Enhanced Cognitive Walkthrough dan HHS Guidelines - Tegar Yoga Prabawakusuma; Niken Hendrakusma Wardani; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Laroslaptop is a provider of buying and selling used laptops, services, and mechanical training. Laroslaptop has a website that is used to promote its services on the internet. The website user interface was evaluated using the enhanced cognitive walkthrough method and was improved based on the HHS guidelines. This method uses 8 experts which divided into 2 groups. 5 novice evaluators and 3 regular specialists. The purpose of this evaluation is to provide recommendations for companies how the appearance of the website interface is better in terms of usability. Evaluation is done by giving task to the evaluators to executed, and asking evaluators to give their opinions on various kinds of problems they find, especially on usability issues. The result is a problem with the selection of words for the menu, menu position, text size on the menu, and the number of menus available. These problems are corrected according to the provisions of the HHS guidelines that will produce improvements in the form of prototypes. After that, a second study was conducted focusing on verification of errors found in the first evaluation. The results was all problems that found before was no longer found in the second evaluation made on the results of the improvement of the website.